Developing French Coursook for Hospitality Students Based on Needs Analysis - Marliza Arsiyana; Viona Amalia (Makassar State University, 2021)
Abstract. Falling into the language for specific purposes area of study, French-language training for hospitality students ideally offers learning materials needed for developing students’ specific language skills in their particular area of specialization. A comprehensive needs analysis then plays a central role in order to design coursebook materials meeting such language skills demands. Therefore, this study was aimed to develop a French-language coursebook with a basic consideration taken from the need analysis process. The framework of this study was Research and Development (R&D) by adopting the Dick & Carey procedures. There were five main procedures, i.e. analyzing the students’ needs, planning (drafting course grid), drafting the coursebook, expert judgment, and revising the coursebook. This research employed two instruments, i.e. questionnaires (for collecting the students’ needs in a need analysis step) and experts’ rubrics (for experts’ judgments). The first step of this study was conducting a needs analysis (NA, hereafter) involving 120 respondents chosen purposively. The data collected through NA questionnaires were analyzed descriptively. The data from NA were used to design the coursebook. Considering the result of experts’ judgments regarding the appropriateness of the content, the appropriateness of language, the appropriateness of materials presented, and the appropriateness of layout presentation, the hospitality coursebook developed is examined as a viable coursebook.Keywords: Needs Analysis, Coursebook, Material Development, French for Specific Purposes, Hospitality